The Nazi Conscience, Claudia Koonz (Cambridge, MA: Harvard University Press, 2003), 368 pp., cloth 29.95, pbk. 16.95 - Leiby, Richard A. (Holocaust and genocide studies, 2006)
In our attempts to understand why the Holocaust, the euthanasia program, and other such atrocities took place, we tend to describe Nazism as antisemitic, anti-modern, and anti-liberal. While it is often convenient to define Nazism by what it was “against,” our knowledge is incomplete unless we also consider what Nazism stood “for.”1 Professor Koonz’s work The Nazi Conscience does precisely that. The author argues that the regime’s intolerance was the by-product of a distinct moral philosophy. The volume is a fascinating new look into the Nazi ethos and the methods the party used to convince the German people of the “righteousness” of its cause., The central theme of the book is the transformation German culture experienced at the hands of the Nazis.